Applications of computer simulation to materials research - Mishra N.S.; Ranganathan S. (My University, 2025)
The applications of computer simulation in materials research are wide and varied. In this paper emphasis is placed on the simulation of microstructures. Simulation has helped us follow the evolution of microstructure on a scale as revealed by the optical microscope. In transmission electron microscopy the matching of simulated and experimental micrographs makes unambiguous characterisation of dislocations possible. In field-ion microscopy, to which the Varanasi group has contributed significantly, the theory of contrast has been pursued primarily with the help of simulated patterns. © 1981 Indian Academy of Sciences.